Lime Pretreatment on Jabon Wood to Improve Its Reducing Sugar Yield - Yusup Amin; Wasrin Syafii; Nyoman J Wistara; Bambang Prasetya (Masyarakat Peneliti Kayu Indonesia, 2014)
The purpose of this study was to determine the performance of enzymatic hydrolysis on lime pretreated jabon wood (Anthocephalus cadamba Miq). Proceeding hydrolysis process, the morphology and crystallinity changes of pretreated jabon were also examined. In the present study, jabon wood meal was put into digester and then lime was loaded at varied lime loading, i.e. at 0.1, 0.3, and 0.5 g Ca(OH)2 g-1 of dry biomass in 90 ml of water. The slurry was then homogenized and heated in the oil bath at 100, 125 and 150 C for 2, 4 and 6 hours. Enzymatic hydrolysis was performed in accordance to the NREL procedures using a cellulase enzyme. The enzyme loading variation was 10, 20 and 40 FPU g-1 of the substrate. the RSY of pretreated jabon increased up to 9.7 folds from that of its control. The highest RSY was obtained for pretreatment with 0.5 g Ca(OH)2 g-1 dried biomass at 150 °C for 4 hours and hydrolyzed with 40 FPU of cellulase (118 mg equivalent glucose g-1 dry biomass). This yield was comparable with 14.4% More than a third of the lignin and hemicellulose content (45.83 and 65.52%) were degraded by lime pretreatment.Keywords: enzymatic hydrolysis, jabon wood, lime pretreatment, reducing sugar yield